The Military Air Transport Service: A first step toward jointness in the United States military, 1948-1966 - Mahoney III, Robert Joseph (Kansas State University, 2020)
Established in 1948, the Military Air Transport Service (MATS) was the first joint command in the United States Department of Defense (DOD) and became a critical first step toward promoting jointness in the United States military. Combining air transport personnel and assets of the United States Air Force and the United States Navy into a single command, the tone in the MATS establishment sharply contrasted with the intense interservice rivalry within the United States military during the late 1940s and early 1950s. At the same time that generals, admirals, and government officials battled over roles, missions, and other resources for their respective services in Washington D.C., MATS proved its effectiveness as a joint command by completing several demanding airlifts—from saving the city of Berlin from a Soviet blockade to establishing the United States’ northernmost air base in the Arctic Circle. Nevertheless, as the importance of strategic airlift for the United States military grew, old problems of rivalry between the Air Force and the Navy and a battle in Congress with the Air Transport Association of America drove MATS toward reorganization into the Air Force’s Military Airlift Command (MAC) in 1966. Despite its status as an Air Force command, MAC continued MATS’ joint legacy by providing air transport for the other services during the Vietnam War. Yet, it was not until 1986 when experiences garnered by the DOD from failures during the Vietnam War and other operations during the early 1980s resulted in a sweeping reorganization of the DOD under the Goldwater-Nichols Act. When the reorganization of the Defense Department established the United States Transportation Command (USTRANSCOM) in 1987 as one of the eleven joint combatant commands, the long road to jointness in the United States military—that had started in 1948 with MATS—was complete.
Keywords: Military Air Transport Service; Jointness; Interservice rivalry; Airlift; Department of Defense; United States Air Force